Towards a common good model of the firm - Abueg, Luisito C. (Animo Repository, 2014)
Business schools that have joined the Principles for Responsible Management Education (PRME) are committed to develop teaching tools and to research on frameworks that can help orient business students towards becoming more socially responsible. The tendency of self-interested models of economics, such as the standard textbook profit maximizing model of the firm, in promoting self-interested behavior among students has been revealed by research. It becomes important, therefore, to develop models of the firm which are more socially oriented. The paper presents a baseline model of the firm which incorporates the provision of living wages and benefits for the employees of the firm and those of its supplier, while pursuing maximum profit. © 2014 by De La Salle University, Philippines.